Вміст цитокінів при хронічній серцевій недостатності з надлишковою масою тіла та ожирінням залежно від фракції викиду лівого шлуночка - Бідзіля, Петро Петрович; Bidzilya, P. P.; Бидзиля, П. П. (My University, 2017)
Метою дослідження було визначення сироваткового вмісту цитокінів інтерлейкіну-6 (IL-6), інтерлейкіну-10 (IL-10), фактору некрозу пухлин-α (TNF-α) та їх співвідношень при ХСН з надлишковою масою тіла та ожирінням залежно від фракції викиду лівого шлуночка (ФВЛШ). Матеріали і методи дослідження. Загалом було обстежено 116 пацієнтів. До основної групи увійшли 104 хворих на ХСН ІІ–ІІІ функціонального класу з нормальною, надлишковою масою тіла та ожирінням І–ІІІ ступеня. Групу порівняння становили 12 пацієнтів з хронічними формами ішемічної хвороби серця, артеріальною гіпертензією без зайвої ваги та клініко-інструментальних ознак ХСН. Відповідно мети дослідження та залежно від ФВЛШ (розраховувалась за методом Симпсона) хворі на ХСН були поділені на 2 підгрупи: зі зниженою ФВЛШ ˂ 45 % (33 хворих) та збереженою ФВЛШ ≥ 45 (71 пацієнт). Розраховуючи індекс маси тіла визначали нормальну, надлишкову масу тіла та ступінь ожиріння. Імуноферментним методом в сироватці крові визначали рівень IL-6, IL-10 та TNF-α. Розрахунковим методом обчислювали співвідношення цитокінів - IL-6/ IL-10 та TNF-α/ IL-10. Today the prevalence of chronic heart failure (CHF) occurs with high mortality in patients despite improved methods of diagnosis and treatment. Probably, this is due to the involvement of new components to the pathogenetic process of CHF which are poorly influenced by conventional therapy. The main pathogenetic factors of CHF were considered the hemodynamic and humoral changes, however, in recent years in the development and progression of the disease proved the role of immune inflammation. Activation of immune-pathologic reactions promotes and contributes to the progression of CHF through an influence on myocardial remodeling, systolic and diastolic function of the left ventricle (LV). One of the most studied markers of immune-pathological changes is proinflammatory and anti-inflammatory cytokines. In patients with CHF demonstrated an increase in blood activity of proinflammatory interleukin- 6 (IL-6), tumor necrosis factor-α (TNF-α) and anti-inflammatory interleukin-10 (IL-10), and the degree of changes directly correlated with disease severity. The traditional predictor of current CHF is LV ejection fraction (LVEF), which reflects myocardial contractility. The presence of low LVEF (systolic dysfunction) is associated with more severe CHF and worse survival of patients. There is an inverse correlation of LVEF and blood levels of proinflammatory IL-6 and tumor necrosis factor-α (TNF-α) and anti-inflammatory IL-10. Last decade, continued increase in the number of patients with overweight and obesity, volume reached worldwide non-infectious epidemic. Obesity is accompanied by structural and functional reorganization of the heart, excessive activation of the inflammatory cytokine cascade, humoral and metabolic disorders, which are the main pathogenic components in the development and progression of CHF. Given the above, a small number of works that have studied the level of serum cytokines in CHF with overweight and obesity depending on LVEF, the chosen direction of research is relevant and timely Purpose - to investigate the serum content of cytokines interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor-α (TNF-α) and their ratios in CHF patients with overweight and obesity depending on left ventricle ejection fraction (LVEF). Materials and methods. Totally 116 patients were examined. The main study group included 104 patients with CHF II–III functional class with normal weight, overweight and obesity I–III degree. The comparison group consisted of 12 patients with chronic forms of ischemic heart disease, arterial hypertension, without overweight, and clinical and instrumental signs of CHF. In accordance with the purpose of the study and depending on LVEF (calculated by Simpson method), patients with CHF were divided into 2 subgroups: with reduced LVEF ˂ 45 % (33 patients) and preserved LVEF ≥ 45 (71 patients). Calculating the body mass index defined normal, overweight and degree of obesity. By ELISA method in the serum was determined the levels of IL-6, IL-10 and TNF-α. With calculation method defined the ratios of cytokines IL-6/IL-10 and TNF-α/ IL-10. Целью исследования было определение сывороточного содержания цитокинов интерлейкина-6 (IL-6), интерлейкина-10 (IL-10), фактора некроза опухолей-α (TNF-α) и их соотношений при ХСН с избыточной массой тела и ожирением в зависимости от фракции выброса левого желудочка (ФВЛЖ). Материалы и методы исследования. Всего было обследовано 116 пациентов. В основную группу вошли 104 больных ХСН ІІ–ІІІ функционального класса с нормальной, избыточной массой тела и ожирением I–III степени. Группу сравнения составили 12 пациентов с хроническими формами ишемической болезни сердца, артериальной гипертензией, без лишнего веса и клинико-инструментальных признаков ХСН. В соответствии с целью исследования и в зависимости от ФВЛЖ (рассчитывалась по методу Симпсона) больные ХСН были разделены на 2 подгруппы: со сниженной ФВЛЖ 45 % (33 больных), и сохраненной ФВЛЖ ≥ 45 (71 пациент). Рассчитывая индекс массы тела, определяли нормальную, избыточную массу тела и степень ожирения. Иммуноферментным методом в сыворотке крови определяли уровень IL-6, IL-10 и TNF-α. Расчетным методом вычисляли соотношение цитокинов - IL-6/ IL-10 и TNF-α/ IL-10.
Content of cytokines in chronic heart failure with overweight and obesity depending on the left ventricle ejection fraction
Содержание цитокинов при хронической сердечной недостаточности с избыточной массой тела и ожирением в зависимости от фракции выброса левого желудочка
Keywords: серцева недостатність; цитокіни; надлишкова вага; ожиріння; фракція викиду лівого шлуночка; heart failure; cytokines; overweight; obesity; left ventricle ejection fraction; сердечная недостаточность; цитокины; избыточный вес; ожирение; фракция выброса левого желудочка